Corrosion inhibition of mild steel in simulated seawater solution by a green eco-friendly mixture of glucomannan (GL) and bisquaternary ammonium salt (BQAS). (15th August 2017) - Luo, Xiaohu; Pan, Xinyu; Yuan, Song; Du, Shuo; Zhang, Caixia; Liu, Yali
Graphical abstract: Schematic illustration of the adsorption formation of GL molecules and BQAS molecules on the mild steel surface in the simulated seawater. Highlights: The mixture of the GL and BQAS can act as a green eco-friendly inhibitor. Corrosion inhibition performance of the mixture was determined. Corrosion inhibition performance of the mixture was much better than that of monocomponent. Adsorption kinetic of the mixture was discussed. Abstract: The corrosion inhibition effect of a green eco-friendly mixture comprised of glucomannan (GL) and bisquaternary ammonium salt (BQAS) on the corrosion protection of mild steel in simulated seawater is investigated by electrochemical measurements and surface characterization. It is found that the mixture of GL and BQAS is a mixed-type inhibitor and can provide effective corrosion inhibition for mild steel. The corrosion inhibition is achieved by the chemical as well as physical adsorption of the mixture on the surface of the steel. It is also found that the adsorption fairly obeys Langmuir isotherm.